PERAN CITRA SEKOLAH DALAM MEMOTIVASI ORANG TUA MEMASUKKAN ANAKNYA KE SEKOLAH DASAR ISLAM TERPADU (SDIT) - Dahlia, Ramadhani; Khairi, Zuriatul; Diniaty, Amirah; Anwar, Khairil; Ahmad Tohar, Ahmaddin; Shofiah, Vivik (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2023)
Quality education outside the home comes from schools that have a good system and education. The increasing number of private schools or integrated Islamic elementary schools (SDIT) that compete to show the superiority of the system, facilities and infrastructure in order to display a good and quality school image, is one of the factors considered and motivated by parents in sending their children to integrated Islamic elementary schools (SDIT). ). The purpose of this research is to describe the role of school image in motivating parents to enroll their children in an integrated Islamic elementary school (SDIT). This study uses a case study qualitative approach where semi-structured interviews are used to collect data from parents who enroll their children in an integrated Islamic elementary school (SDIT). The sample in this study were parents enrolling their children in an integrated Islamic elementary school (SDIT) Rumbai Pekanbaru. The results of this study show that a quality school image is needed by a school. This is a consideration for parents when they decide to choose a school, because one of the motivations of parents to send their children to SDIT Al-Ittihad Rumbai Pekanbaru is that they want their children to study in good schools with good quality schools so that their children get good learning methods and become memorizer of the Qur'an with Islamic character.